Pengaruh Brand Awareness terhadap Minat Beli: Peran Mediasi Persepsi Kualitas pada Produk I-Quit-Ordinary-Smoking (IQOS) - Dika Ananda, Muhammad Fahri; Henryanto, Aria Ganna (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2024)
Smokers are always looking for other alternatives to replace cigarettes such as using vape and heated tobacco products (IQOS) because they are proven to have low health risks. The purpose of this study was to determine the effect of brand awareness on purchase intention through perceived quality on IQOS. The population of this study are IQOS users in Surabaya. Samples were taken using purposive sampling method. The data analysis method used is PLS (Partial Least Square) with SmartPLS 3 software. The results of this study indicate that: (1) Brand Awareness has a positive and significant influence on purchase intention (2) Brand Awareness has a positive and significant influence on perceived quality (3) Perceived Quality has a positive and significant influence on purchase intention (4) Perceived Quality mediates the relationship between brand awareness and purchase intention.